(untitled) (International Journal of Environmental Sciences, 2025)
Introduction: Diabetes Mellitus poses a significant global challenge, notably increasing the risk of comorbidities and complications. Medication adherence, a significant modifiable factor plays a vital role in the effective management of diabetes. Promoting medication adherence can delay the progression of depressive symptoms, as poor adherence is associated with diminished quality of life. The study aims to evaluate the Quality of Life in individuals with Type 2 Diabetes Mellitus and to explore the connection between the severity of depressive symptoms and medication adherence. Methodology: In this cross-sectional study, a total of 101 individuals diagnosed with Type 2 Diabetes Mellitus were recruited. Medication Adherence was assessed using Medication Adherence Rating Scale (MARS). Quality of Life was evaluated using the WHOQOL-BREF Questionnaire, while the severity of depressive symptoms was assessed with the Hamilton Depression Rating Scale (HDRS). Results: Patients with lower MARS scores demonstrated significantly higher HDRS scores (r = -0.270, p= 0.006), indicating an inverse relationship between medication adherence and depressive symptoms. Regression analysis revealed that medication adherence accounted for 7.3% for the variance in depressive symptoms (F(1,99) = 7.805, p= 0.006). Higher HDRS scores were significantly associated with lower physical and psychological domain scores on the WHOQOL-BREF (r= -0.522 and r= -0.566 respectively, both p <0.001). Conclusion: Implementing strategies to enhance medication adherence will effectively delay the progression of depressive symptoms among Type 2 diabetes patients. Better management of depressive symptoms can lead to improved quality of life for this population.